Reading with the Machine: AI as a Pedagogical Partner for Critical Digital Literacy and Human Interpretation in Literature Classrooms - Riyad Md. Arefin Sohan; Sajib Khandaker; Md. Mahmudunnabi Sourov (Journal of English for Academic and Specific Purposes (JEASP), 2026)
The study elucidates how Critical Digital Literacy (CDL) in the literature classroom for interpretation can be developed by integrating AI tools. This paper finds that AI can serve as a pedagogical collaborator in Literature classes, particularly for Bangladeshi students from the Department of English. This research paper explores how the integration of AI can enhance human interpretative autonomy in the literature classes without over-reliance on technology assistance. This article argues that undergraduate students can enhance their literary interpretative skills and creativity by integrating AI tools, as in today’s fast-paced modern world, AI has become an integral part across various sectors. Employing a mixed-method research design, this study adapts qualitative and quantitative approaches to investigate the role of AI as a collaborative partner in the literature classroom. Few existing studies have examined AI's contribution to fostering CDL within literature classes. Therefore, the present study addresses the gap by demonstrating how AI can effectively function as a collaborative partner.